Microneedles and micropump for drug delivery applications - Teo, Melissa Ai Ling (2008)
In this project, arrays of hollow/solid microneedles were microfabricated out of silicon. In vitro experiments using isolated rat's skin demonstrated that these arrays enhance drug permeability by 10-20 times with the amount of enhancement depending on the microneedle diameter. Valveless diffuser micropumps were also fabricated for drug delivery applications.